PENGARUH MEDIA SOSIAL TERHADAP PERILAKU BELAJAR SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW (SLR) - Ayunda Nursensa Wandira; Asep Sahrul Gunawan (STKIP Subang, 2026)
The development of digital technology and social media has significantly transformed the learning behavior of elementary school students in the digital era. The high intensity of social media use among children has become an important issue because it generates both positive and negative impacts on the learning process. Social media is not only used for entertainment and communication but has also become a medium for digital learning. However, uncontrolled use of social media may affect students’ concentration, academic discipline, and learning achievement. This study aims to analyze the influence of social media on elementary school students’ learning behavior through a Systematic Literature Review (SLR) approach. The study employed a descriptive qualitative method by analyzing 25 national journals indexed by SINTA and international reputable Q1 journals published between 2020 and 2025. Data collection was conducted through article searches in Google Scholar, Garuda, DOAJ, ResearchGate, and ScienceDirect using relevant keywords. Data analysis applied the PRISMA stages, including identification, screening, eligibility, and inclusion. The findings revealed that social media has a significant influence on students’ learning behavior. Positive impacts include increased creativity, learning motivation, access to information, and interactive digital learning. Meanwhile, negative impacts include decreased concentration, low academic discipline, gadget addiction, and declining academic achievement. This study contributes to the development of elementary education research in the digital era and emphasizes the importance of parental and teacher supervision in children’s social media use. Future studies are recommended to apply quantitative or mixed methods approaches to obtain more comprehensive findings.